Resposta :
Respostas
e
Explicação:
S = -15 -2t + 6t²
S = So + vot + 1/2at²
So = -15 m
vo = -2 m/s
1/2a = 6
a = 6.2
a = 12 m/s²
A) v= vo + at
v = -2 + 12 t
B)
S = -15 - 2t + 6t²
S = -15 -2.5 + 6.5²
S = -15 -10 + 6.25
S = -15 - 10 + 150
S = 125 m
C)
S = -15 - 2t + 6t²
a = 6
b = -2
c = -15
t = - b +- Vb² - 4.a.c/2.a
t = -(-2) +- V(-2)² - 4.6.(-15)/2.6
t = 2 +- V4 + 360/12
t = 2 +- V364/12
t = 2 +- 19,07/12
t = 2 + 19,07/12 = 21,07/12 = 1,75 s
t1 = 2 - 19,07/12 = =17,07/12 = =1,42 s (não serve) não tem tempo negativo